2020
DOI: 10.1007/s10068-020-00789-5
|View full text |Cite|
|
Sign up to set email alerts
|

Food-derived coagulase-negative Staphylococcus as starter cultures for fermented foods

Abstract: Food safety is of significant concern to consumers and is a major issue for the food industry. As such, the industry is aware of the importance of safety assessments of starters used in the production of fermented foods. Coagulase-negative staphylococci (CNS) are the predominant bacteria found in fermented foods worldwide. Because of this, food-derived CNS are used as starters for cheese and meat fermentation, and have been investigated for use as starters in soybean fermentation. Although food-derived CNS are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 94 publications
(187 reference statements)
0
34
0
Order By: Relevance
“…Notably, coagulase negative Staphylococcus species have been reported as the predominant species of bacteria in fermented foods worldwide. Species of Staphylococcus are used as microbial starters in cheese, meat, and soybean fermentation [43]. Importantly, a few species of Staphylococcus are also known to be food borne pathogens for humans and other animals [44].…”
Section: Bacterial Community Compositionmentioning
confidence: 99%
“…Notably, coagulase negative Staphylococcus species have been reported as the predominant species of bacteria in fermented foods worldwide. Species of Staphylococcus are used as microbial starters in cheese, meat, and soybean fermentation [43]. Importantly, a few species of Staphylococcus are also known to be food borne pathogens for humans and other animals [44].…”
Section: Bacterial Community Compositionmentioning
confidence: 99%
“…Many studies have reported acquired resistance to erythromycin and tetracycline among lactic acid bacteria (LAB) and coagulase negative staphylococci (CNS), and therefore, their corresponding genetic determinants are considered an important potential cause of the horizontal spread of antibiotic-resistant (AR) genes between different bacterial species [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The genes encoding for tyrosine decarboxylase, histidine decarboxylase, lysine decarboxylase, and ornithine decarboxylase were also found missing from the two K. rhizophila isolates, in line with the observation of their non-producing phenotype for the biogenic amines. Genome sequencing of food-derived S. carnosus , S. equorum , S. succinus , and S. xylosus isolates showed that they all carried lysine decarboxylase-encoding genes required for cadaverine production, and none carried genes involved in histamine and tyramine production ( Heo et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%